Voltage changes in electrical micro network with hybrid power plant - Varetsky, Yuriy; Horban, Vitalii (Lviv Polytechnic Publishing House, 2016)
The paper presents the study results on renewable energy hybrid system within a micro grid which is tied to bulk power system. The voltage variations character has been analyzed considering mode of wind generator reactive power control. Optimal reactive power control requirements are shown in consideration of voltage variation mitigation.
Keywords: renewable energy hybrid system; wind generator; photovoltaic panels; reactive power control; electrical network voltage variations